Vibration and acoustic noise of industrial inductors associated to converters in the railway domain: Design and material impacts. Issue 6 (7th November 2016) - Iamamura, Bruno; Rossi, Mathieu; Hecquet, Michel; Lanfranchi, Vincent; Recorbet, Sylvain; Tridon, Florence
Abstract : Purpose: The purpose of this paper is to present an original study of industrial inductors with different air-gap materials in order to reduce the vibration and noise of inductors. Acoustic comfort is an increasingly important factor at the design stage of industrial inductors associated to converters. In addition, power converters in the railway domain are more and more compact and powerful. Design/methodology/approach: Experiments, simulations and test devices were used to determine the main physical phenomena that generate the undesirable audible noise. Electric and vibratory measurements (modal and operational analysis) were compared with the numerical calculations. PWM and sinusoidal supply were taken into account and different prototypes with different materials in the air-gap were built. Findings: This study analyzes and details the origin of the electromagnetic noise due to the vertical mode, in order to reduce the vibration and noise of inductors. A detailed analysis using finite element simulation and experimental measurements of free-free mode or forced mode under electrical excitation was conducted to interpret the vibrations of the structure. In addition, in order to observe trends and the impact of magnetostriction effect, the authors propose a simplified model. Practical implications: Electric and vibratory measurements (modal and operational analysis) are compared with the numerical calculations. Originality/value: This paper gives a response about the origin of the noise with different experimental measurements. Changing the air-gap material is beneficial for the deflection of the inductor. However, it has been presented that, following the shape of the inductor, it is beneficial to reduce or increase the stiffness of the material depending on the column height. For a fixed Young's modulus air-gap, a ratio Column height/air-gap thickness exists, which makes it possible to cancel the deflection.